Determinan Pengungkapan Tanggung Jawab Sosial Perusahaan (CSR) Pada Perusahaan Manufaktur Industri Barang Konsumsi di BEI 2014-2018 - Estu Mahanani; Mery Wanialisa (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to determine the determinants of corporate social responsibility (CSR) disclosure, namely leverage, company size, and industry sensitivity. The population in this study are consumer goods industrial manufacturing companies listed on the Indonesia Stock Exchange (IDX), as many as 47 companies. The sample in this study used a purposive sampling technique as many as 19 companies. The results of this study indicate that based on the partial test (t test), the variables Leverage, Firm Size, and Industry Sensitivity have a positive and significant effect on Corporate Social Responsibility (CSR) Disclosure. Simultaneously (f test) proves that, Leverage, Company Size and Industrial Sensitivity have an effect on Disclosure of Corporate Social Responsibility (CSR) in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018.